URGENSI HUKUM ADAT DALAM PEMBAHARUAN HUKUM PIDANA DI INDONESIA - DESI APRIANI (Jurnal Ilmu Hukum, 2015)
Long before the various forms oflegal entry into the archipelago,people who lived since thebeginning of civilization in thisarchipelago (Indonesia) have hadas a regulator kehidupan.Hal lawis in line with the expression ofCicero, Ubi Societas ibi originalius.Hukum as a regulator of thelife that is born from an idea(thought), the heart and soul ofthe people who later termed byexperts with state law Lifeadat.Dalam customary law cannot be separated from theestablishment and development ofnational law, including criminallaw pidana.Hukum Dutchheritage which is not inaccordance with the culturalvalues and personality societymust be renewed by taking thematerial of customary law thatcriminal law can be effective andideal, because the ideal of nationallaw is a national law thatresponsive.